KEMAMPUAN MENULIS TEKS EKSPLANASI SMP NEGERI 25 PEKANBARU - Winarti '; Nursal Hakim; Abdul Razak (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This Research aim to to know the Ability Write The Text of Explanation of Student of Class of VII SMP Country 25 Pekanbaru. Method used in this research is descriptive method, that is method weared to explain the data obtained in research as it is. this Research technique use the technique tes write the text explanation. Description of result of this research in the form of: (1) according to title of text explanation, (2) according to public Statement, (3) according to consecution explaining / special statement, (3) according to interpretation. this Research target is to description ability write the text of explanation of student of class of VII SMP Country 25 Pekanbaru in aspect of title of text eksplanation, public statement, consecution penjelas / special statement, and interpretation. this Subyek research Population is 164 student, while this sampel research is 41 student. Result from this research indicate that (1) ability write the title categorize to lower, (2) ability write the public statement categorize the medium, (3) ability write the consecution penjelas / special statement categorize the medium, and (4) ability write the epilogue categorize medium.keyword : writing, explanation text, publicability, consecution explanation, interpretation